The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.4257/oeco.2022.2603.06
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGAÇÃO SOBRE O COMÉRCIO ILEGAL DE Procambarus clarkii GIRARD, 1852 (DECAPODA: CRUSTACEA) NA REGIÃO SUL DO BRASIL

Abstract: A temática das invasões biológicas tem sido muito debatida nos últimos 20 anos. Estudos demonstram que uma das principais vias de introdução de espécies aquáticas é de origem antrópica, principalmente para fins alimentícios e aquariofilia. Das 481 espécies exóticas invasoras (EEI) já identificadas no Brasil, Procambarus clarkii, conhecido como lagostim-vermelho-da-Louisiana, é uma das mais preocupantes por possuir diversas características biológicas e ecológicas que a torna um invasor perigoso. Apesar de ter s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The establishment of this species has already been demonstrated in Brazil ( Loureiro et al, 2015 ) with evidence of negative impacts on native fauna ( Banci et al, 2013 ) and it has been hypothesized that the introduction occurred through fish keeping ( Magalhães et al, 2005 ; Magalhães & Andrade, 2014 ). Despite imports, transportation, and commercialization of P. clarkii being prohibited in the country for more than two decades ( IBAMA, 2008 ), a recent study showed that the species is still freely commercialized by aquarium stores ( Smialoski & Almerão, 2022 ), which makes clear the ineffectiveness of this legislation.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of this species has already been demonstrated in Brazil ( Loureiro et al, 2015 ) with evidence of negative impacts on native fauna ( Banci et al, 2013 ) and it has been hypothesized that the introduction occurred through fish keeping ( Magalhães et al, 2005 ; Magalhães & Andrade, 2014 ). Despite imports, transportation, and commercialization of P. clarkii being prohibited in the country for more than two decades ( IBAMA, 2008 ), a recent study showed that the species is still freely commercialized by aquarium stores ( Smialoski & Almerão, 2022 ), which makes clear the ineffectiveness of this legislation.…”
Section: Discussionmentioning
confidence: 99%